CTIM-24. AUTOLOGOUS CD34+ ENRICHED HEMATOPOIETIC PROGENITOR CELLS GENETICALLY MODIFIED FOR HUMAN INTERFERON-α2, ARE WELL TOLERATED & RAPIDLY ENGRAFT IN PATIENTS WITH GLIOBLASTOMA MULTIFORME (TEM-GBM_001 STUDY). (9th November 2020) - Finocchiaro, Gaetano; Gentner, Bernhard; Eoli, Marica; Francesca, Farina; Anghileri, Elena; Girlanda, Stefania; Carrabba, Matteo; Cuccarini, Valeria; DiMeco, Francesco; Legnani, Federico; Pollo, Bianca; Bruzzone, Maria Grazia; et al.
Abstract: GBM with an unmethylated MGMT gene promoter is associated with very poor prognosis. A subset of tumor associated macrophages expressing the angiopoietin receptor Tie2 (TEMs) can be genetically modified for local & tumor restricted release of interferon-α2 (IFN). IFN has antitumor effects, inhibits angiogenesis & modulates the immune system. Temferon consists of autologous HSPCs transduced ex-vivo with an LVV encoding an IFN gene & expression control sequences for TEMs. TEM-GBM is an open-label, Phase I/IIa study (Part A: 3x3x3 dose escalation; Part B: n=12), & Temferon (single dose) is given to patients with first diagnosis of GBM & unmethylated MGMT promoter. Part A 3 rd cohort is ongoing & completes dosing in September 2020. Eight patients completed screening; one patient died (disease progression) before Temferon was administered. Six patients received Temferon (3 women, 3 men, mean age 52.3 years). Cohort 1 received Temferon 0.5x10 6 cells/kg & Cohort 2, 1x10 6 cells/kg. Neutropenia & thrombocytopenia occurred as expected following conditioning & hematologic recovery (HR) occurred median D+13. Transduced PBMCs were identified by vector copy number (VCN) on myeloid cells at HR & at later timepoints. In general, a dose-ordered increase in VCN was observed (mean VCN D+30 CD14+ Cohort 1: 0.094, cohort 2: 0.125); 1 patient in each cohort had low VCNs. VCN remained detectable up to recent follow up visits (≤ D+180). No dose-limiting toxicities have been reported. Four SAEs occurred in 3 patients who received Temferon (pneumonia, pulmonary embolism, febrile neutropenia, fatigue) but these events were not attributed to Temferon, resolved, & may have been related to the conditioning regimen (carmustine & thiotepa). Disease progression has been confirmed in 3 patients who received Temferon. These preliminary results indicate feasibility of engrafting a pre-determined fraction of Temferon cells in the bone marrow of GBM patients without, so far, causing dose-limiting toxicity.